UK national study of barriers to renal transplantation in children. Issue 4 (2nd April 2020) - Kim, Ji Soo; Marlais, Matko; Balasubramanian, Ramnath; Muorah, Mordi; Inward, Carol; Smith, Graham C; Reynolds, Ben C; Yadav, Pallavi; Morgan, Henry; Shenoy, Mohan; Tse, Yincent; Hussain, Farida; et al.
Abstract : Aims: To investigate access to paediatric renal transplantation and examine potential barriers within the process. Methods: Cross-sectional, multicentre, observational study where paediatric nephrology centres in the UK were requested to provide data on transplantation plans for all children (<18 years) with end-stage kidney disease (ESKD). Results: 308 children with ESKD were included in this study from 12 out of 13 UK paediatric nephrology centres. 139 (45%) were being prepared for living donor transplantation and 82 (27%) were listed for deceased donor transplantation. The most common cited factors delaying transplantation from occurring in children were disease factors (36%), donor availability (27%) and size of the child (20%). Psychosocial factors were listed as a barrier in 19% of children. Conclusions: In this study we have documented the main barriers to renal transplantation in children. Some identified factors may be modifiable through local or national intervention, including donor availability and patient psychosocial factors.